Short-term effects of brachycephalic obstructive airway syndrome surgery on fitness and exercise in brachycephalic dogs - Goossens, Juliette; Meyer-Lindenberg, Andrea; Zablotski, Yury; Schroers, Maike (Frontiers in Veterinary Science, 2025)
IntroductionBrachycephalic obstructive airway syndrome (BOAS) significantly impacts the physical fitness of affected dogs. This study aimed to assess changes in physical fitness, as measured by vital signs and salivary cortisol and vasopressin concentrations, before and after BOAS surgery using a standardized fitness test.MethodsA prospective clinical study was conducted on 35 brachycephalic dogs, including 13 Pugs, 21 French Bulldogs, and one English Bulldog. A preliminary examination included clinical anamnesis and a general examination. Physical fitness was evaluated using a submaximal treadmill test consisting of three 5-minute runs followed by a recovery phase. Vital signs were monitored throughout the test and saliva samples were taken before, immediately after and 15 min after the test. Eighteen animals underwent surgery due to moderate to severe BOAS symptoms, while 17 animals that were free of symptoms were assigned to the control group.ResultsOne month post-OP (post-operatively), dogs that underwent BOAS surgery exhibited significant improvement in physical fitness based on vital signs. However, they remained significantly less fit than the control group. No statistically significant changes were observed in salivary cortisol or vasopressin concentrations before and after surgery.DiscussionBOAS surgery reduces clinical symptoms and improves physical fitness, but affected dogs continue to exhibit substantial limitations. The consistency of cortisol and vasopressin levels across both groups reinforces the hypothesis of a stress-induced HPA-axis dysfunction, yet the limited number of evaluable samples and external influences suggest that salivary stress hormones alone may not reliably indicate surgical success. Future studies should incorporate additional biomarkers and clinical assessments to better understand the physiological impact of BOAS and its treatment.